Fluorescence Spectroscopy and 13C NMR Spectroscopy Characteristics of HA in Black Soil at Different Corn Straw Returning Modes - Shuang Zheng; Sen Dou; HongMei Duan; BoYan Zhang; Yue Bai (International Journal of Analytical Chemistry)
A three-year field experiment was conducted to analyze the effects of straw enrichment and deep incorporation on the humus composition and the structure of humic acid (HA) in black soil. The differences in the HA structure between different straw returning methods were detected by three-dimensional fluorescence spectroscopy and 13C NMR technology. The purpose of this paper is to provide a theoretical basis and data support for improving the straw returning system. Four different treatments, including no straw applied (CK), straw mulching (SCR), straw deep ploughing (MBR), and straw enrichment and deep incorporation (SEDI: harvested the corn straw from four rows together with a finger-plate rake and then crushed and buried them in one row in the 20∼40 cm deep level in the subsoil with a wind-driven input cylindrical plough), were used in this study. Our results showed that compared to CK treatment, SEDI significantly increased the contents of organic carbon (SOC), soil humic acid carbon (HAC), fulvic acid carbon (FAC), and humin C content (HM-C) in the subsurface soil layer by 27.47%, 34.33%, 19.66%, and 31.49%, respectively. Among all the straw returning treatments, SEDI treatment had the most significant effect in increasing the contents of HEC, HAC, and FAC. Straw returning not only reduced the degree of condensation and oxidation of the HA structure but also increased the proportion of alkyl C and enhanced the hydrophobicity of the HA structure in subsurface soil. Moreover, SEDI treatment significantly increased the proportion of aliphatic C/aromatic C of the HA structure in subsurface soil and improved the aliphatic property of HA, which had a significant effect on the HA structure compared to other treatments.